Can The Value of an Unquoted Company Be Determined Accurately? A case study of a Technology Company in the UK - PAL, SOUVIK (2015)
In the case of a Merger or an Acquisition, a key element is to conduct the valuation of the target company. There are different types of valuation techniques that have been used by both practitioners and researches to determine what could be the price that would be effectively suitable for the transaction and simultaneously be acceptable to both the parties of the transaction. Although most of the techniques used for company valuation have a broad definition for listed companies, which can be tailored to suite specific cases, it could become challenging to accurately replicate such techniques for small unquoted companies. Consequently the impact is on the determination of what could be an acceptable transaction price during the Acquisition or Merger of an unquoted firm. This case study based work within the technology and telecommunication sector, looked at the possibility of accurately determining the value of an unquoted firm based in the UK, by using income based and the market based valuation approach and concludes that it is not possible to determine the value of an unquoted firm accurately.